Understanding autism. Experiencing autism by blogging self-advocates - Pufund, Dorota (Understanding Disability: Issues, Research, Reflections, 2021)
The text presents a reconstruction of the experience of autism by blogging self-advocates. The starting point is the concept of autobiographical self-learning. The study included a qualitative analysis of the content of open blogs on the Internet, whose authors are people who declare themselves to be autistic. The analysis was conducted on the basis of the grounded theory. MAXQDA software was used.